Impact of micro-alloying in ion-irradiated nickel: From the inhibition of point-defect cluster diffusion by thermal segregation to the change of dislocation loop nature. (1st March 2023) - Ma, Kan; Décamps, Brigitte; Huang, Liangzhao; Schäublin, Robin E.; Löffler, Jörg F.; Fraczkiewicz, Anna; Nastar, Maylise; Prima, Frédéric; Loyer-Prost, Marie
Abstract: Micro-alloying strongly affects the incubation period of void swelling in irradiated face-centered cubic materials. However, the underlying mechanism, which relates to the formation of dislocation loops, is still unclear. Here, we investigate pure Ni, Ni-0.4wt.%Cr and Ni-0.4/0.8/1.2wt.%Ti as model materials, to gain insight into the solute effects on the loops evolution in the early stage of irradiation. The dislocation loop characteristics (mobility, Burgers vector, nature) are studied using in-situ transmission electron microscopy and ex-situ irradiation with Ni + ions at 450°C and 510°C for doses from 0.06 to 0.7 dpa. It appears that a tiny amount of Ti effectively increases the loop density, reduces the loop mobility and the stacking fault energy. It leads to an equal distribution among a /2<110> perfect loop families. It also stabilizes self-interstitial loops against vacancy loops depending on Ti content and temperature. Our modeling of radiation-induced segregation, based on experiments and recent ab initio calculations of flux couplings, predicts a Cr enrichment and a Ti depletion nearby dislocation loops. It is in good agreement with our observations by X-ray spectroscopy in TEM and by atom probe tomography. However, the lowered loop mobility must be the signature of a thermal segregation rather than the impact of radiation-induced depletion. Indeed, oversized Ti atoms subsequently trapped at strained lattice sites around the dislocation line of the loop due to thermal segregation would inhibit its diffusion. This opens new perspectives for future experimental investigations and radiation-effect modeling. Graphical abstract: Image, graphical abstract